Conditional Lethality of recA and recB Derivatives of a Strain of Escherichia coli K-12 with a Temperature-Sensitive Deoxyribonucleic Acid Polymerase I - Monk, M. (1972)
We have isolated a strain of Escherichia coli K-12 carrying a mutation, polA12, that results in the synthesis of a temperature-sensitive deoxyribonucleic acid (DNA) polymerase I. The double mutants polA12 recA56 and polA12 recB21, constructed at 30 C, are inviable at 42 C. About 90% of the cells of both double mutants die after 2 hr of incubation at 42 C. Both double mutants filament at 42 C and show a dependence on high cell density for growth at 30 C. In polA12 recB21 cells at 42 C, DNA and protein synthesis gradually stop in parallel. In polA12 recA56 cells, DNA synthesis continues for at least 1 hr at 42 C, and there is extensive DNA degradation. The results suggest that the primary lesion in these double mutants is not in DNA replication per se.